Di Bawah Bayang-Bayang Nikel: Multi-Dampak Tata Kelola Pertambangan di Perbatasan Konawe–Konawe Utara, Indonesia - Selvia Junita Praja; Serly Wulandari; Tumpak Haposan Simanjuntak; Ihwan Sudrajat; Rossy Lambelanova (Society, 2025)
Decentralization in Indonesia is designed to strengthen local development. Yet, the prolonged boundary dispute between Konawe and North Konawe Regencies reveals a governance paradox in which resource abundance within contested territories generates cascading multidimensional impacts. This qualitative case study employs purposive sampling of government officials, electoral supervisors, community leaders, and industry actors, with data collected through semi-structured interviews, field observations, and documentary analysis, and processed in NVivo 12 using iterative coding. The findings demonstrate that unresolved territorial fragmentation, compounded by intensive nickel mining, produces a multi-impact cascade: environmental degradation manifested in flooding, soil erosion, water and air pollution; economic uncertainty that constrains welfare distribution; social tensions arising from labor absorption and demographic shifts; political vulnerabilities such as duplication risks in the Final Voters List (DPT); and governance stagnation in land administration and investment. By advancing the concept of local spatial geopolitics of mining, this study shows how boundary disputes create a governance vacuum that amplifies ecological, economic, social, political, and administrative risks, and calls for joint-boundary management mechanisms, strengthened environmental regulation, and coordinated law enforcement to restore legitimacy and resilience in mining regions.